INTERNALISASI KARAKTER PEDULI LINGKUNGAN MELALUI MANAJEMEN SAMPAH BERASIS 6R - Diah Listyarini (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The character of caring for the environment is an important part of the effort to create a sustainable environment so it needs to be passed on to the next generation. Schools are a means of internalizing important values in shaping the character of caring for the environment in the younger generation, especially students. The process of internalizing the character of caring for the environment is currently still focused on subjects in schools that are related to the environment. Therefore, schools have an important role in implementing the internalization of environmental care characters. One of the implementations of the environmental care character is to carry out 6R-based waste management, namely reducing, reusing, replacing, separating, recycling, and composting. The purpose of this activity is to increase students' awareness of the environment (environmental care character) and increase students' insight and skills in managing waste in the school environment. This activity was carried out for 6 months. This activity is carried out on a bottom-up basis using methods of counseling, mentoring, training, and evaluation. This activity consists of six stages of activities: (1) socialization of environmental care character and school waste management; (2) Demonstration of garbage selection; (3) demonstration of composting; (4) Compost monitoring assistance; (5) Compost harvesting; and (6) Evaluation of activities. The result of this activity is that participants understand the character of caring for the environment, implementing waste management, separating waste, and making compost.